REVEALING THE CAPITAL STRUCTURE FACTOR IS DOMINATED BY DEBT TO LQ45 COMPANIES ON THE INDONESIA STOCK EXCHANGE - Masidonda, Jaelani La; Hariyati, Tri Retno; Hariyanti, Dwi (Universitas Brawijaya, Indonesia, 2023)
Capital structure has an important role that must be determined to improve the welfare of the owner or the value of the company. Many studies have been done before about capital structure. This study aims to analyze the effect of Chief Executive Officer (CEO) ability, return on investment, return on equity and profit margin on capital structure. This study includes a database outside of accounting data, namely CEO Ability. This is important to study to determine the ability of the CEO in providing internal sources of funds in the capital structure of LQ45 companies on the Jakarta Stock Exchange which are more dominated by debt. The method used is a mixed method between quantitative methods and qualitative methods. The quantitative method uses multiple linear regression analysis. While qualitative methods are used to analyze the influence based on the results of interviews. The object of research was conducted on 45 companies included in the LQ45 stock list on the Indonesia Stock Exchange with a sample of 31 companies. The reasons for selecting 31 samples: a) the company has been listed on the IDX during the 2017-2021 research period, b) has financial statements with non-negative retained earnings and equity. The results showed that CEO ability, profit margin, return on investment as a factor causing capital structure is dominated by debt, while return on equity has no effect on capital structure. The implication of this research is that CEOs who are less able to increase profits to meet the availability of internal funds, the company must meet funding needs sourced from debt through good net working with fund owners.